An American in Scotland - Connelly, Lucy (Connelly, Lucy. Scottish Isle mystery, 2023)
The small idyllic town of Sea Isle, Scotland, harbors some dark secrets, and Dr. Emilia McRoy is determined to uncover all of them--no matter what the diagnosis in this charming cozy.